AI IN THE MEDICAL FIELD: TRANSFORMING HEALTHCARE THROUGH INNOVATION - Erkinboev Sardorbek Ravshanbek o’g’li; Khasanov Akhmadjon Odiljon o’g’li; Erkinboyeva Madinabonu Afzaljon qizi; Scientific supervisor: Dilshod Shomirzaevich Tulanov (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Artificial Intelligence (AI) has emerged as a powerful tool in various industries, and its potential in the medical field is immense. This thesis explores the applications of AI in healthcare and its impact on patient care, diagnosis, treatment, and medical research. By leveraging AI algorithms, machine learning, and deep learning techniques, healthcare providers can enhance efficiency, accuracy, and decision-making processes. This paper delves into the benefits and challenges associated with implementing AI in the medical field, while also discussing ethical considerations and potential future developments.